Respostas
respondido por:
7
x² + 5x - 6 = 0
Δ = 5² - 4 . 1 . (-6)
Δ = 25 + 24
Δ = 49
x = (-5+-√49)/2
x = (-5+-7)/2
x' = (-5-7)/2 => -12/2 => -6
x" = (-5+7)/2 => 2/2 => 1
S = {-6, 1}
respondido por:
5
Vamos lá
X² + 5x - 6 = 0
A = 1
B = 5
C = -6
Δ = b² - 4 • a • c
Δ = 5² - 4 • 1 • ( -6)
Δ = 25 + 24
Δ = 49
X = ( -b ± √ Δ) / 2 • a
X = ( -5 ± √ 49 ) 2 • 1
X = ( - 5 ± 7 ) 2
X1 = - 5 + 7 / 2 = 2 / 2 = 1
X2 = - 5 - 7 / 2 = - 12/ 2 = -6
S { 1, - 6 }
X² + 5x - 6 = 0
A = 1
B = 5
C = -6
Δ = b² - 4 • a • c
Δ = 5² - 4 • 1 • ( -6)
Δ = 25 + 24
Δ = 49
X = ( -b ± √ Δ) / 2 • a
X = ( -5 ± √ 49 ) 2 • 1
X = ( - 5 ± 7 ) 2
X1 = - 5 + 7 / 2 = 2 / 2 = 1
X2 = - 5 - 7 / 2 = - 12/ 2 = -6
S { 1, - 6 }
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás